The effect of combined diet containing n-3 polyunsaturated fatty acids and silymarin on metabolic syndrome in rats - Poruba, Martin; Anzenbacher, Pavel; Rácová, Zuzana; Oliyarnyk, Olena; Hüttl, Martina; Malínská, Hana; Marková, Irena; Gurská, Soňa; Kazdová, Ludmila; Večeřa, Rostislav (Physiological research, 2019)
The risk of development of metabolic syndrome can be increased by hypertriglyceridemia. A search for effective therapy is a subject of considerable attention. Therefore, our hypothesis is that the fish oil (containing polyunsaturated fatty acids; n-3 PUFA) in a combination with silymarin can more effectively protect against hypertriglyceridemia-induced metabolic disturbances. The study was conducted using a unique non-obese strain of rats with hereditary hypertriglyceridemia an accepted model of metabolic syndrome. Adult male rats were treated with n-3 PUFA (300 mg/kg/day) without or with 1 % micronized silymarin in a diet for 4 weeks. The treatment with the diet containing n-3 PUFA and silymarin significantly reduced concentrations of serum triglycerides (-45 %), total cholesterol (-18 %), non-esterified fatty acids (-33 %), and ectopic lipid accumulation in skeletal muscle (-35 %) compared to controls. In addition, an increase in Abcg5 and Abcg8 mRNA expression (as genes affecting lipid homeostasis) as well as in protein content of ABCG5 (+78 %) and ABCG8 (+232 %) transporters have been determined in the liver of treated rats. Our findings suggest that this combined diet could be used in the prevention of hypertriglyceridemia-induced metabolic disorders.
Keywords: Animals; Fatty Acids, Omega-3; Antioxidants; Rats, Wistar; oxidační stres; Dyslipidemias; Fish Oils; lipidy; Oxidative Stress; Metabolic Syndrome; Silymarin; Lipid Metabolism; Lipids; metabolický syndrom; metabolismus lipidů; peroxidace lipidů; dieta; omega-3 mastné kyseliny; Lipid Peroxidation; Diet; Male; modely nemocí na zvířatech; silymarin; antioxidancia; dyslipidemie; Disease Models, Animal; krysa rodu Rattus; Hypertriglyceridemia; exprese genu; zvířata; mužské pohlaví; rybí oleje; Rats; hypertriglyceridemie; Gene Expression; potkani Wistar